Implications of global environmental change for the burden of snakebite. (July 2021) - Martín, Gerardo; Yáñez-Arenas, Carlos; Rangel-Camacho, Rodrigo; Murray, Kris A.; Goldstein, Eyal; Iwamura, Takuya; Chiappa-Carrara, Xavier
Abstract: Snakebite envenoming is a set of intoxication diseases that disproportionately affect people of poor socioeconomic backgrounds in tropical countries. As it is highly dependent on the environment its burden is expected to shift spatially with global anthropogenic environmental (climate, land use) and demographic change. The mechanisms underlying the changes to snakebite epidemiology are related to factors of snakes and humans. The distribution and abundance of snakes are expected to change with global warming via their thermal tolerance, while rainfall may affect the timing of key activities like feeding and reproduction. Human population growth is the primary cause of land-use change, which may impact snakes at smaller spatial scales than climate via habitat and biodiversity loss (e.g. prey availability). Human populations, on the other hand, could experience novel patterns and morbidity of snakebite envenoming, both as a result of snake responses to environmental change and due to the development of agricultural adaptations to climate change, socioeconomic and cultural changes, development and availability of better antivenoms, personal protective equipment, and mechanization of agriculture that mediate risk of encounters with snakes and their outcomes. The likely global effects of environmental and demographic change are thus context-dependent and could encompass both increasing and or snakebite burden (incidence, number of cases or morbidity), exposing new populations to snakes in temperate areas due to "tropicalization", or by land use change-induced snake biodiversity loss, respectively. Tackling global change requires drastic measures to ensure large-scale ecosystem functionality. However, as ecosystems represent the main source of venomous snakes their conservation should be accompanied by comprehensive public health campaigns. The challenges associated with the joint efforts of biodiversity conservation and public health professionals should be considered in the global sustainability agenda in a wider context that applies to neglected tropical and zoonotic and emerging diseases. Graphical abstract: Image 1 Highlights: Distribution and abundance of snakes are expected to be affected by climate change. Land-use change may also impact snakes but at smaller spatial scales than climate. Human populations could experience novel patterns and morbidity of snakebite. Reducing snakebite should be accompanied by actions that protect snake diversity.